Afrikanermynwerkers en die Mynwerkersunie, 1936-1948 : II : Die hervormingsorganisasie in die Mynwerkersunie, 1937-1948 (Historia, 2021)
Afrikaner Mine Workers and the Mine Workers' Union. 1936 1948 Between the years of 1936 and 1948 a bitter struggle waged in the ranks of the white Mine Workers Union (MWU) for control of this large and influential organisation. In essence it was a struggle of the unskilled and semi-skilled Afrikaner mine workers against the gross maladministration of the Union management. This struggle was, however, organised and fanned from the outside by Afrikaner political and cultural leaders (""Die Nasionale Raad van Trustees"" or NRT) in an attempt to mobilise the Afrikaner workers for party political and Afrikaner national interests. Their vehicle was the ""Afrikanerbond van Mynwerkers"" (ABM) -which, as an opposing Christian national union, tried to oust the MWU. The first serious attempt was warded off by reinstating the closed shop principle and thus making a second union illegal. Thereafter the ABM tried to reform the MWU from within and during a lengthy struggle succeeded in bringing the maladministration of the MWU in the open. In 1947 the struggle was won when a new Afrikaner dominated board of management was elected. The article focuses on the role of the NRT and ABM and the ways, in which it mobilised support from Afrikaners, the majority of whom did not have the same strong feelings of nationhood as the leaders of the ABM/NRT.Die Afrikanerbond van Mynwerkers (ABM) se pogings in die loop van 1936 en 1937 om 'n alternatiewe vakbond in die lewe te roep om die Mynwerkersunie (MWU) te onttroon, is deur die instelling van die geslote werplaasbeginsel op 1 Junie 1937 gekelder. Volgens hierdie reëling was alle mynwerkers verplig om as lede van die MWU, nou die enigste wettige vakbond, te registreer of die gevaar te loop om ontslaan te word. Teoreties het die ABM op 1 Junie 1937 ontbind, maar die ABM/NRT (Nasionale Raad van Trustees) was steeds vasberade om Charles Harris en sy mede-amptenare van die MWU te beveg. Om dit te doen, is daar op 'n nuwe strategie besluit, nl. dat alle lede van die ABM by die MWU moes aansluit en dat hulle die MWU van binne sou hervorm. Die ABM sou dus sy werksaamhede voortsit en nie amptelik as 'n "aparte" groep binne die MWU funksioneer. In die proses het dit ook spoedig van naam verander en as die Hervormingsorganisasie bekend gestaan.
Keywords: Nasionale Raad van Trustees; History; Geskiedenis; Mine Worker's Union; Industrial relations; Afrikanerbond of Mine Workers; Afrikanerbond van Mynwerkers; ABM; Mynwerkersunie; MWU; 1936; 1936-1948; NRT; Historia